2021
DOI: 10.1088/1361-648x/abe8f9
|View full text |Cite
|
Sign up to set email alerts
|

Absence of local moments in the kagome metal KV3Sb5 as determined by muon spin spectroscopy

Abstract: We have carried out muon spin relaxation and rotation measurements on the newly discovered kagome metal KV3Sb5, and find a local field dominated by weak magnetic disorder which we associate with the nuclear moments present, and a modest temperature dependence which tracks the bulk magnetic susceptibility. We find no evidence for the existence of V4+ local moments, suggesting that the physics underlying the recently reported giant unconventional anomalous Hall effect in this material warrants further studies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 26 publications
(52 reference statements)
5
75
0
Order By: Relevance
“…CsV 3 Sb 5 features Z 2 band topology and a two-stage symmetry breaking: a CDW transition at T CDW ∼ 95 K with a subsequent superconducting transition at T C ∼ 2.7 K 10-14 . The CDW order with inverse star-of-David pattern involves 2 × 2 and concurs with the CDW order despite the lack of long-range magnetic ordering 10, 12,15,[17][18][19] .…”
Section: Introductionsupporting
confidence: 57%
“…CsV 3 Sb 5 features Z 2 band topology and a two-stage symmetry breaking: a CDW transition at T CDW ∼ 95 K with a subsequent superconducting transition at T C ∼ 2.7 K 10-14 . The CDW order with inverse star-of-David pattern involves 2 × 2 and concurs with the CDW order despite the lack of long-range magnetic ordering 10, 12,15,[17][18][19] .…”
Section: Introductionsupporting
confidence: 57%
“…Since the present muon spin rotation experiments show direct evidence for the absence of local moments of the Ru atom in LaRu 3 Si 2 , this kagome system is different from high-T c superconductors or spin liquid compounds. It is rather on the side of itinerant kagome or hexagonal systems such as (Cs,K)V 3 Sb 5 [53] or even 2H-NbSe 2 [46], where μSR shows the absence of magnetic correlations. On the other hand, the system LaRu 3 Si 2 does not exhibit a CDW ground state unlike the superconductors (Cs,K)V 3 Sb 5 [54].…”
Section: Resultsmentioning
confidence: 99%
“…The superconducting transition temperature Tc is 0.93, 0.92, and 2.5 K for A = K, Rb, and Cs, respectively [2][3][4] . While there are no local magnetic moments 12 , these V-based superconductors manifest a charge density wave (CDW) order at 78, 103, and 94 K, respectively [1][2][3][4] . Interestingly, for KV3Sb5, high-resolution scanning tunneling microscopy (STM) study demonstrated that such charge order in the frustrated Kagome lattice is topological 5 , which leads to a giant anomalous Hall effect 6 , and can also be a strong precursor of unconventional superconductivity 5 .…”
Section: Introductionmentioning
confidence: 99%